Treatment of arteriosclerotic diseases of the carotid artery. The carotid stent - Grunwald, I; Papanagiotou, P; Roth, C; Hartmann, K; Ahlhelm, F; Reith, W (2008)
In order to find the most suitable therapy concept for patients with severe stenosis of the carotid bifurcation (>70%), knowledge on the currently available treatment methods is necessary. In addition to carotid endarterectomy, medication therapy and stent angioplasty are also available. The outcome after stent angioplasty must be considered under the aspects of rapid technical development and increasing experience. Results of studies are still only of limited value with respect to the development of protection systems, flexible guiding catheters, low profile and more visible stents and balloons as well as using thrombocyte aggregation. © 2008 Springer Medizin Verlag.